نظرة المدربين لدور والاختبارات والقياسات في عملية الانتقاء الرياضي لدى لاعبي كرة القدم أقل من 17سنة - شادلي, عبد الوهاب; يوسف, بن عودة (Institut d’Éducation Physique et Sportive mostaganem 2021/2022, 2021)
ﻋﻨوان اﻟد ارﺴﺔ " اﻟﻤدرﺒﻴن ﻟدور الإختبارات واﻟﻘﻴﺎﺴﺎت ﻓﻲ ﻋﻤﻠﻴﺔ اﻻﻨﺘﻘﺎء اﻟرﻴﺎﻀﻲ ﻟدى ﻻﻋﺒﻲ ﻛرة اﻟﻘدم ﻓﺌﺔ 17 ﺴﻨﺔ " ﺘﻬدف اﻟد ارﺴﺔ إﻟﻰ ﻤﻌرﻓﺔ اﻷﺒﻌﺎد اﻟﺘﻲ ﺘﺄﺨذﻫﺎ اﻻﺨﺘﺒﺎ ارت واﻟﻘﻴﺎﺴﺎت أﺜﻨﺎء ﻤرﺤﻠﺔ اﻻﻨﺘﻘﺎء اﻟرﻴﺎﻀﻲ وﻤدى ﺘﺄﺜﻴر اﻟﻛﻔﺎءة اﻟﺘدرﻴﺒﻴﺔ واﻟﻤﺴﺘوى اﻟﻌﻠﻤﻲ ﻟﻠﻤدرﺒﻴن ﻓﻲ ﻫذﻩ اﻟﻌﻤﻠﻴﺔ ٬ اﻟﻔرض اﻷﺴﺎﺴﻲ ﻓﻲ اﻟد ارﺴﺔ للإختبارات دور ﻓﻲ ﻋﻤﻠﻴﺔ اﻨﺘﻘﺎء ﻻﻋﺒﻲ ﻛرة اﻟﻘدم ﻓﺌﺔ أﻗﻝ ﻤن 17 ﺴﻨﺔ ٬ ﺘم اﺨﺘﻴﺎر ﻤدرﺒﻲ ﻛرة اﻟﻘدم ﻟﻔﺌﺔ اﻗﻝ ﻤن 17 ﺴﻨﺔ ﻟوﻻﻴﺔ ﻏﻠﻴ ازن ﻛﻌﻴﻨﺔ ﻟﻠﺒﺤث ﺒطرﻴﻘﺔ ﻋﺸواﺌﻴﺔ وﻴﻘدر ﻋددﻫم ﺒـ 21 ﻤدرب إذ ﻗﻤﻨﺎ ﺒﺘوزﻴﻊ اﺴﺘﻤﺎرة اﺴﺘﺒﻴﺎﻨﻴﻪ ﻋﻠﻴﻬم واﺴﺘﻨﺘﺠﻨﺎ أن اﻻﻋﺘﻤﺎد ﻋﻠﻰ الإختبارات اﻟﺒدﻨﻴﺔ واﻟﻤﻬﺎرﻴﺔ واﻟﻨﻔﺴﻴﺔ أﻤر ﻀروري ﻓﻲ ﻋﻤﻠﻴﺔ ﺘﺤدﻴد اﻟﻤواﻫب اﻟﺸﺎﺒﺔ واﻨﺘﻘﺎﺌﻬﺎ وأﻴﻀﺎ ﻛﻔﺎءة اﻟﻤدرﺒﻴن ﺘﻠﻌب دور ﻫﺎم ﻓﻲ اﻟﻌﻤﻠﻴﺔ اﻻﻨﺘﻘﺎﺌﻴﺔ واﺴﺘوﺼﻴﻨﺎ ﻓﻲ آﺨرﻫﺎ ﻋﻠﻰ ﻀرورة إﺘﺒﺎع اﻟطرق اﻟﻌﻠﻤﻴﺔ أﺜﻨﺎء ﻋﻤﻠﻴﺔ اﻻﻨﺘﻘﺎء وذﻟك ﻟن ﻴﻛون إﻟﻰ ﺒﺎﺨﺘﻴﺎر ﻤدرﺒﻴن ذو ﻛﻔﺎءة ﻟﻬذﻩ اﻟﻌﻤﻠﻴﺔ. The title of the study “Trainers for the role of tests and measurements in the sports selection process for 17-year- old football players” The study aims to know the di mensions that tests and measurements taken during the sports selection stage and the extent to which the training efficiency and scientific level of trainers influence this process. The process of selecting football players under 17 years of age, football coaches for a category under 17 years of age were selected for the state of Relizane as a sample for research in a random manner. They are estimated at 21 coaches. We distributed a questionnaire to them and concluded that relying on physical, skill and psychological tests is essential in the process of Identification and selection of young talents, as well as the efficiency of trainers, plays an important role in the selective process. In the end, we recommended the need to follow scientific methods during the selection process, and this will only be done by selecting qualified trainers for this process.
LES-2022-13
Keywords: اﻟﻤدرب اﻟرﻴﺎﻀﻲ– اﻻﺨﺘﺒﺎ ارت واﻟﻘﻴﺎﺴﺎت-اﻻﻨﺘﻘﺎء اﻟرﻴﺎﻀﻲ – ﻛرة اﻟﻘدم / Sports coach - tests and measurements - sports selection - football.